Sources and seasonality of long-chain diols in a temperate lake (Lake Geneva). (June 2021) - Lattaud, Julie; Balzano, Sergio; van der Meer, Marcel T.J.; Villanueva, Laura; Hopmans, Ellen C.; Sinninghe Damsté, Jaap S.; Schouten, Stefan
Highlights: 1, 13- and 1, 15-diols are seasonally produced during water-column stratification. 1, 13- and 1, 15-diols are likely produced by several species of eustigmatophytes. Diatoms are unlikely to be 1, 14-diol producers in Lake Geneva. Abstract: Long-chain diols (LCDs) are lipids commonly found in freshwater environments. They are produced in lake waters and in low water-flow regions of rivers but their sources and the controls on their abundance are poorly constrained. To be able to use LCD as environmental proxy (e.g. for reconstructing lake temperature and as a freshwater indicator in marine systems) we need to understand the sources of these LCDs and the processes controlling their abundance and distribution. Therefore, we performed a seasonal study of suspended particulate matter in Lake Geneva, a temperate lake at the border of France and Switzerland in 2017–2018. LCDs were most abundant in lake surface water from late spring to early autumn, coinciding with the thermal stratification of the water column. Their distribution varied throughout the year, which points towards multiple producers. Incubation of lake water with 13 C-labelled bicarbonate only showed uptake of inorganic carbon in LCDs during their peak seasonal abundance. An 18S rRNA gene amplicon analysis revealed that eustigmatophytes, known producers of LCDs, are present in Lake Geneva and show the same seasonal trend in abundance as the LCDs, indicating that these algae are likely the most important producers of LCDs in this lake. In combination with previous studies our results suggest that LCDs show potential to trace changes in lake water-column stratification, and validate the use of the C32 1, 15-diol as a proxy for freshwater input from rivers and lakes in marine sediments.